Experimental approach to reduce uncertainty in estimating the thermal performance of buildings’ envelopes in hot climates - Nourhan M. Waly; Hamdy Hassan; Ryo Murata; David J. Sailor; Hatem Mahmoud (Developments in the Built Environment)
This study aims to reduce uncertainty in key thermal performance parameters of Cooling Load Temperature Difference CLTD and U-values used to estimate the energy demand of buildings in hot arid regions. A developed methodology that combines experimental and mathematical approaches is employed. A coupled experimental approach (QIRT/THM) is introduced with modifications to improve the results accuracy. The experimental approach achieved up to 93% correlation coefficient with the standard data estimation. Despite the high correlation, estimated cooling loads using tabular data and the experimental values, hold a potential difference of up to 36%. A correction equation was suggested to narrow the calculations gap under specific context. These findings could have substantial implications for reducing uncertainty by standardizing the thermal performance of buildings. Recognizing the substantial impact of building envelopes, the findings contribute to more accurate estimations which play a significant role in narrowing the Energy Performance Gap in hot climate regions.